Impact of global value chain embedding on industrial environmental performance: An empirical study based on the countries along the “Belt and Road” - Li, Yan; Wang, Yuhao; Zhang, Xiaohan; Huang, Qingbo (Frontiers in Environmental Science, 2022)
Global value chain (GVC) embedding is a “Double-edged sword”. While the countries along the “Belt and Road” benefit from the dividends brought by GVC embedding, the environmental pollution caused by industrial production becomes increasingly severe due to the lack of core technology and weak research and development (R&D) capability. Environmental performance can comprehensively reflect the cleaner production level of the industry considering the interaction of various input factors. With the deepening of GVC embedding in countries along the “Belt and Road”, it is essential to improve industrial environmental performance from the perspective of GVC embedding. Based on the industrial sector data from 15 countries along the “Belt and Road” during the period from 2007 to 2020, the impacts of GVC embedding on industrial environmental performance are empirically examined in this study using the feasible generalized least squares (FGLS) and panel threshold model. The findings of this study could shed light on industrial pollution emission reduction measures through GVC embedding for the “Belt and Road” countries. Specifically, the results manifest that: 1) The increase of GVC forward embedding promotes industrial environmental performance, while the increase of GVC backward embedding has an inhibitory effect. 2) The impact of GVC position on industrial environmental performance shows a evident threshold effect with respect to the intensity of environmental regulation. In other words, when a country’s environmental regulation intensity rises continuously and crosses the threshold value, the upgrade of the GVC position will promote industrial environmental performance. 3) The effect of GVC embedding on industrial environmental performance is heterogeneous. From the perspective of cross-border times of added value, GVC backward simple embedding inhibits industrial environmental performance, while GVC backward complex embedding is promotive. From the perspective of time heterogeneity, the implementation of the “Belt and Road” Initiative has changed the impact of GVC backward embedding on environmental performance from inhibition to promotion. In the end, this paper provides policy implications for countries along the “Belt and Road” to establish a green and low-carbon circular development system and achieve the goal of industrial clean production.